The Impacts of Openness and Global Value Chains on the Performance of Turkish Sectors - Yanıkkaya, Halit; Altun, Abdullah; Tat, Pınar (Panoeconomicus, 2024)
Regarding the dynamics of the contemporary world economy, success in a domestic economy cannot be achieved without effective integration policies for goods/services and capital flows. To evaluate this proposition, we utilize many openness measures for two periods, 1995–2009 and 2000–2014, for the Turkish sectors. The empirical findings suggest that domestic value added in export is a major driver of sectoral value added. While import and backward linkages appear to be stimulators for total factor productivity (TFP) in manufacturing industries, they have no significant impact on sectoral value added. Trade barriers in the form of tariff rates, which primarily stemmed from manufacturing industries, have a considerable detrimental impact on Turkish sectoral performance. Higher tariffs not only make it more difficult for Turkish businesses to enter overseas markets but also raise the costs for importers. The initial impact of this protection is inexorably exacerbated by global value chains (GVCs), with negative consequences felt in nearly every economy. Given the increased backward GVC involvement of some manufacturing industries, such as machinery and equipment, Turkish sectors should be prepared for external shocks by diversifying importer origins, stocking up, and boosting transparency in their operations. Overall, designing and implementing trade policies to effectively integrate into the GVCs is an important task for Turkey. Keywords: Openness, Sectoral total factor productivity, Value added, GVC participation, Turkey. JEL: F14, F21, O14, O24, O47